2004
DOI: 10.1029/2004jd004557
|View full text |Cite
|
Sign up to set email alerts
|

General circulation model estimates of aerosol transport and radiative forcing during the Indian Ocean Experiment

Abstract: [1] Aerosol sources, transport, and sinks are simulated, and aerosol direct radiative effects are assessed over the Indian Ocean for the Indian Ocean Experiment (INDOEX) Intensive Field Phase during January to March 1999 using the Laboratoire de Météorologie Dynamique (LMDZT) general circulation model. The model reproduces the latitudinal gradient in aerosol mass concentration and optical depth (AOD). The model-predicted aerosol concentrations and AODs agree reasonably well with measurements but are systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 43 publications
8
76
0
Order By: Relevance
“…Previous studies though confined to the winter period to understand the source regions of aerosol origin during Indian Ocean Experiment intensive field phase (INDOEX-IFP) (January to March 1999) have identified, several regions like Indo-Gangetic Plain, central India, south India, Africa, west Asia and north west India that have a large influence on the aerosol characteristics over the Indian Ocean region (Verma et al 2007). Previous studies using satellite data and models have shown that south Asia and the Indian subcontinent region are major contributors to the aerosol loading over the Indian Ocean region (Nair et al 2003;Reddy et al 2004). The BC mass reported for Port Blair in Andaman and Nicobar Islands in the Bay of Bengal to the east of Indian landmass, was higher than those observed at Minicoy.…”
Section: Black Carbon Aerosolmentioning
confidence: 99%
“…Previous studies though confined to the winter period to understand the source regions of aerosol origin during Indian Ocean Experiment intensive field phase (INDOEX-IFP) (January to March 1999) have identified, several regions like Indo-Gangetic Plain, central India, south India, Africa, west Asia and north west India that have a large influence on the aerosol characteristics over the Indian Ocean region (Verma et al 2007). Previous studies using satellite data and models have shown that south Asia and the Indian subcontinent region are major contributors to the aerosol loading over the Indian Ocean region (Nair et al 2003;Reddy et al 2004). The BC mass reported for Port Blair in Andaman and Nicobar Islands in the Bay of Bengal to the east of Indian landmass, was higher than those observed at Minicoy.…”
Section: Black Carbon Aerosolmentioning
confidence: 99%
“…While the sources of these emissions are relatively well-known, there are large uncertainties in emission estimates across inventories (e.g., Jena et al, 2015;Zhong et al, 2016). Indeed, correctly simulating the extremely high PM 2.5 abundances in the IGP has proved troublesome for current global chemistry models (Reddy et al, 2004;Mian Chin et al, 2009;Ganguly et al, 2009;Menon et al, 2010;Henriksson et al, 2011;Goto et al, 2011;Nair et al, 2012;Cherian et al, 2013;Moorthy et al, 2013;Sanap et al, 2014;Pan et al, 2015). A multi-model evaluation by Pan et al (2015) concluded that an underestimation of wintertime biofuel emissions was the dominant cause of the models' low biases.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol transport and its impact on radiative forcing were estimated over the tropical Indian Ocean during INDOEX (Krishnamurty et al, 1998;Podgorny et al, 2000;Rajeev et al, 2001). General circulation model (GCM) simulations over south Asia during the INDOEX period with the high resolution regional emissions information (Reddy et al, 2004;Verma et al, 2008Verma et al, , 2012 indicate the likely contribution of emissions from regions outside India to aerosol loading over the Indian subcontinent and adjoining oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated aerosols loading was observed in a remote marine environment over the Arabian Sea during INDOEX 1999. The chemical transport models have been used widely for atmospheric simulations over southern Asia during the INDOEX period (Rajeev et al, 2000;Rasch et al, 2001;Podgorny and Ramanathan, 2001;Reddy et al, 2004;Verma et al, 2008Verma et al, , 2012, and have shown a predominance of sulphate in the south Asian region. Most of the INDOEX studies emphasize the underestimated impact of aerosols on climate Ramanathan et al, 2002;UNEP, 2002).…”
Section: Introductionmentioning
confidence: 99%